2015
DOI: 10.3109/10428194.2015.1041385
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography, thrombin generation test and thrombodynamics reveal hypercoagulability in patients with multiple myeloma

Abstract: Patients with multiple myeloma (MM) are at increased risk of venous thromboembolism. Therefore, adequate laboratory control of hemostasis and subsequent adjustments of anticoagulant therapy are necessary. We studied hemostasis changes using thromboelastography (TEG), thrombin generation test (TGT) and thrombodynamics (TD) in primary MM patients (PMMpt, n=25) and patients in remission (RMMpt, n=34) during blood stem cell (BSC) mobilization. TD and TEG reveal hypercoagulability in PMMpt (*p<0.05) in relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 34 publications
3
27
1
7
Order By: Relevance
“…Our results obtained with TF 5 PM were consistent with those of Tiong et al who found significantly elevated velocity index and shorter TtPeak in 24 patients compared with 48 controls . Another study found no significant differences in TG parameters between 25 patients and 33 healthy subjects …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results obtained with TF 5 PM were consistent with those of Tiong et al who found significantly elevated velocity index and shorter TtPeak in 24 patients compared with 48 controls . Another study found no significant differences in TG parameters between 25 patients and 33 healthy subjects …”
Section: Discussionsupporting
confidence: 93%
“…Our results obtained with TF 5 PM were consistent with those of Tiong et al who found significantly elevated velocity index and shorter TtPeak in 24 patients compared with 48 controls. 14 Another study found no significant differences in TG parameters between 25 patients and 33 healthy subjects 8. With 1 PM TF, no significant difference was found between patients with and controls, which was in agreement with Leiba et al study comparing 13 patients to 14 controls 12.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Some of the clinical and pharmacological results obtained with it are shown in Fig. 7, and more can be found in recent reports and reviews [67,[80][81][82][83][84][85][86].…”
Section: Spatial Coagulation: Possible Applications Beyond Basic Resementioning
confidence: 87%